Perspectivas simbólicas em a filha perdida: explorando os labirintos da maternidade por meio da boneca e outras metáforas - Fonseca, Karla Mariana Gondim (2024)
This research aims to analyze Elena Ferrante's novel A filha perdida (2016), exploring the rich symbolism present in the narrative. Among the various symbolic elements addressed, our focus will be primarily directed towards the role played by dolls, understanding their meaning, function, value, and relevance to the development of the plot and the construction of the characters. To achieve this goal, we will adopt an interdisciplinary approach that combines the principles of literary criticism, comparative literature, and psychoanalysis. In this sense, we will discuss Sigmund Freud's concepts of Unheimlich (the Uncanny) and Doppelgänger (the Double), examining how the presence of dolls in the narrative may refer to these psychoanalytic notions and enrich the understanding of the characters' internal conflicts. Additionally, we will draw on Carl Gustav Jung's analytical perspective to explore possible archetypal aspects present in the representations of dolls and motherhood and how they reflect the characters' individuation processes. Finally, we will also employ the theory of psychoanalyst Donald Woods Winnicott to understand how the past and its interpersonal relationships are determining factors in the construction of their personalities and the significance of dolls within this context. With this integrated approach, we aim to elucidate the deep layers of meaning present in the narrative, enriching the understanding of the symbolic nuances that pervade the entire novel.